Creative Economy Development Efforts in Culinary Business - Arif Rachman Putra; Ernawati Ernawati; Jahroni Jahroni; Tri Seno Anjanarko; Eli Retnowati (Journal of Social Science Studies (JOS3), 2022)
The government has declared the creative economy to be the foundation of the regional economy. This statement is evidenced by the continued development of the creative economy in Indonesia. It was recorded that in 2021 the creative economy contributed 1.274 trillion rupiah. With this result, the government will be optimistic about its original goal. The creative economy of the culinary sector is one of the 17 sectors launched in Indonesia. The culinary sector contributes 41% to the GDP of the creative economy. With this increase, it is necessary to know what factors have an impact on increasing the creative economy of the culinary sector. Indonesia has many culinary delights spread throughout its territory. So that people do not have difficulty in determining the product they want to sell. The community is expected to be able to innovate to produce products that are packaged modernly by maintaining the existing taste. Creative economy business actors are also expected to be able to overcome obstacles with their creative ideas.